PENDIDIKAN AGAMA ISLAM PADA ANAK USIA SEKOLAH DASAR DALAM KELUARGA DI KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Rianawati, Wasli (Conciencia, 2019)
Family roles have a huge influence on child education. The roles of each parent must complement each other, so that harmonization in the family can be realized through religious values in daily life. Family become the first place for education for a child, so the Islamic education in the family is very important because it will shape the child's personality. This study used a qualitative descriptive research method, so the results of this research were narrated in the form of descriptions. The data were gathered through observation and interviews where the major respondents were parents in Pemangkat. The data from the interview were analysed simultaneously, so that the data verification was also done simultaneously. The findings of this study revealed that the first religious education for the child was in the form of teaching things that are easy to understand, e.g. pronouncing asthma Allah, becoming close friends with them, forming good habit, encouraging the children to seek science by studying in the mosques. The widespread religious understanding in the family was later found in Pemangkat that Islamic educational materials were taught to children such as educational beliefs, religious education, moral education, primary teaching of Islamic education and reading the Qur'an. In Pemangkat, it was found that Islamic education in the family must pay attention to the Islamic faith, where faith is the essence of the foundation of faith one must be given to the child from an early age. In educating the children, the parents provided materials about religion to children that is by using the method of storytelling, by giving examples, experiences and punishment.